Glucocorticoid Receptor α Mediates Roflumilast’s Ability to Restore Dexamethasone Sensitivity in COPD - Reddy, Aravind T (Int J Chron Obstruct Pulmon Dis, 2020)
BACKGROUND: Glucocorticoids are commonly prescribed to treat inflammation of the respiratory system; however, they are mostly ineffective for controlling chronic obstructive pulmonary disease (COPD)-associated inflammation. This study aimed to elucidate the molecular mechanisms responsible for such glucocorticoid inefficacy in COPD, which may be instrumental to providing better patient outcomes. Roflumilast is a selective phosphodiesterase-4 (PDE4) inhibitor with anti-inflammatory properties in severe COPD patients who have a history of exacerbations. Roflumilast has a suggested ability to mitigate glucocorticoid resistance, but the mechanism is unknown. METHODS: To understand the mechanism that mediates roflumilast-induced restoration of glucocorticoid sensitivity in COPD, we tested the role of glucocorticoid receptor α (GRα). Roflumilast’s effects on GRα expression and transcriptional activity were assessed in bronchial epithelial cells from COPD patients. RESULTS: We found that both GRα expression and activity are downregulated in bronchial epithelial cells from COPD patients and that roflumilast stimulates both GRα mRNA synthesis and GRα’s transcriptional activity in COPD bronchial epithelial cells. We also demonstrate that roflumilast enhances dexamethasone’s ability to suppress pro-inflammatory mediator production, in a GRα-dependent manner. DISCUSSION: Our findings highlight the significance of roflumilast-induced GRα upregulation for COPD therapeutic strategies by revealing that roflumilast restores glucocorticoid sensitivity by sustaining GRα expression.